The comparison of outcomes of solifanacin plus behavioral therapy versus Mirabegron alone in management of overactive bladder - Muhammad Sajjad; Syed Atif Hussain; Muhammad Saddiq Haris; Aqib shahzad; Shafi ghouri; Muhammad Zohaib Fazal (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE:  Overactive bladder is a prevalent condition that significantly impacts patients' quality of life. While pharmacological treatments are commonly used, combining medication with behavioral therapy may offer enhanced symptom management. The aim of this study is to compare the outcomes of a combination treatment—solifenacin plus behavioral therapy versus mirabegron alone in the management of Overactive Bladder.METHODOLOGY: This is an Experimental study conducted in Out-patient department of Urology, Sheikh Zayed Hospital, Rahim Yar khan on 60 patients, diagnosed with persistent over active bladder symptoms. Group I was given Solifenacin combined with behavioral therapy and Group-Il was given mirabegron alone for 12 weeks. The micturition, episodes of urgency and episodes of nocturia per 4 hours were assessed in both groups. Data was analyzed using SPSS 25.0.RESULTS: In the study, mean age of sample was 52.4 ± 13.2 years. The mean micturition frequency was reduced from baseline 9.872 ± 0.215 in the Solifenacin group and 9.800 ± 0.278 in the Mirabegron group to 4.760 ± 0.129 vs 6.283 ± 0.029 (p≤0.001) after 12 weeks. The nocturia frequency per 24 hours changed from 2.065 ± 0.33 vs 2.410 ± 0.48 to 0.520 ± 0.16 vs 0.180 ± 0.07 (p<0.01) and urgency episodes per 24 hours changed from 2.065 ± 0.331 vs 2.410 ± 0.482 to 0.180 ± 0.078 0.520 ± 0.162(p≤0.001) respectively.CONCLUSION: The combination of Solifenacin and behavioral therapy offers a more effective and holistic approach to managing OAB symptoms compared to Mirabegron alone.